Transformation of Santri Identity in the Era of Globalization: A Systematic Literature Review of Cultural Hybridity, Digitalization, and Pesantren Resilience - Amalia Nasir; Tri Wahyudi Ramdhan; Mufaizin Mufaizin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Amidst the massive escalation of globalization and the phenomenon of digital disruption, the identity of santri (Islamic boarding school students) is undergoing a fundamental transformation from traditional-exclusive patterns toward a more dynamic, adaptive, and hybrid identity construction. This study aims to comprehensively map the dynamics of santri identity transformation using a Systematic Literature Review (SLR) of various reputable scientific literatures. By implementing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, 14 primary articles published between 2021 and 2026 were analyzed in-depth through qualitative synthesis techniques. The findings identify three main pillars of identity shift: (1) the internalization of information technology, such as the implementation of the Santri Identity Card (SIC) and the Pedatren management system, which have transformed into new instruments for data-based character discipline (digital behavioral control); (2) the emergence of a